ANALYSIS OF ASCORBIC ACID AND BORAX USING PURPLE SWEET POTATO EXTRACT AS A COLORIMETRIC SENSOR IN FOOD AND DRINKS USING DIGITAL IMAGES - Ainun Mardiyah As-Salimah; Sutarno Sutarno; Ariefa Primair Yani; Bhakti Karyadi; M Luthfi Firdaus (Jurusan Kimia FMIPA Universitas Lampung, 2024)
The addition of ascorbic acid and borax to food and drinks if it exceeds the threshold limit can have dangerous effects on consumers. This research aims to create a simple and fast but accurate method for analyzing ascorbic acid and borax, using purple sweet potato extract as a colorimetric sensor and quantitative analysis using digital images. The results of the digital image have an accuracy of 99% with LOD (Limit of Detection) of 1.96% and LOQ (Limit of Quantity) with a value of 6.53% for ascorbic acid. As for borax, the LOD is 0.54% and the LOQ is 1.78%. Semi-quantitative tests for ascorbic acid and borax in food and drinks can be carried out using a cotton test kit. The wet noodle food sample tested (purchased from around the Bengkulu University campus) was proven not to contain borax because there was no color change. However, the packaged drink tested positive for ascorbic acid as indicated by a color change from purple to pink.